Effect of an anti‐gonadotropin‐releasing factor vaccine on sexual and aggressive behaviour in male pigs during the finishing period under Australian field conditions. Issue 4 (April 2015) - Karaconji, B; Lloyd, B; Campbell, N; Meaney, D; Ahern, T
Abstract : Objective: The objective of this study was to evaluate the effectiveness of an anti‐gonadotropin‐releasing factor vaccine in controlling sexual and aggressive behaviour of male pigs in the late finishing period under Australian field conditions. Methods: Male pigs from four consecutive batches over a 4‐month period were randomly assigned to two groups: an untreated control group (n = 434) or a group treated with Improvac® (n = 433). The vaccine was administered at 10 and 16 weeks of age. Pigs were housed under commercial conditions in ecoshelters, a commonly used housing system in Australia in which pigs are kept in large pens often containing >100 animals. The occurrence of sexual and aggressive behaviours was recorded and evaluated after second vaccination until slaughter at 22 weeks of age. Results: Male pigs treated with Improvac demonstrated significant reductions in mounting, fighting, pushing, head butting and tail manipulation when compared with control animals. Conclusion: This study confirms that vaccination with Improvac can improve the welfare of entire male pigs by inhibiting sexual and aggressive behaviour.